Assessment of fish communities in a Mediterranean MPA: Can a seasonal no-take zone provide effective protection?. (31st July 2018) - Dimitriadis, Charalampos; Sini, Maria; Trygonis, Vasilis; Gerovasileiou, Vasilis; Sourbès, Laurent; Koutsoubas, Drosos
Abstract: The efficacy of a Mediterranean Marine Protected Area (National Marine Park of Zakynthos – NMPZ, Ionian Sea, Greece) that implements a seasonal no-take zone as part of its management scheme was assessed using fish data collected in situ with underwater visual census. Sampling was conducted at two habitat types ( Posidonia oceanica meadows and rocky reefs) that occur at sites of different protection level with respect to fisheries (high protection: seasonal no-take zone within the MPA; intermediate: zones within the MPA where small-scale fishing is allowed; none: areas outside the MPA, where all types of fishing are allowed, including trawlers, purse seiners, and recreational fishing). The data were used to examine the effects of protection level and habitat type on community parameters, trophic structure and functional diversity of fish populations that occupy the upper sublittoral zone. Overall, habitat type had a more pronounced effect than protection level on all investigated parameters. Biomass, density and number of fish species with low commercial value were higher in sites of intermediate protection, but no substantial fisheries-related ecological benefits were detected for targeted fish in the seasonal no-take zone. Conducted 8 years after the initial implementation of the seasonal no-take management scheme, our study suggests that existing fishing regulations in the NMPZ provide some measurable effects, but fall short of maintaining sufficient protection for the recovery of apex predators or other commercially important fish species. A revision of the existing zoning system to include permanent no-take zones, alongside the regulation of professional fishing and all extractive activities in the rest of the MPA, are strongly encouraged in order to enhance the effectiveness of fisheries management.